The concept of kafa'ah as the pre-requirement of Banjar community marriage - Anwar Hafidzi; Nurdin Nurdin (Sultang Agung Islamic University, 2020)
This research will discuss the concept and practice of Kafa'ah (capable) when going to a marriage procession in the Banjar community based on the An-Nikah Book of Shaykh Muhammad Arsyad Al-Banjary. Kafa'ah basically in marriage is equality of degrees in choosing a prospective wife or husband when going to a marriage contract. However, for the Banjar community, kafa'ah is used as a benchmark in choosing a partner. The solution is with this research because it was written in the 17th century AD as a basis for the use of kafa’ah in Islamic law in general. The method used in this research is a literature study with a primary source of the Book of An-Nikah by Sheikh Muhammad Arsyad al-Banjary. The results of this study found that the concept of kafa'ah offered to the Banjar community in the 17th century was based on their ability to carry out their obligations as husbands and religious responsibilities.